The Impact of Inquiry Learning and Discovery Learning Models on Mathematical Communication Skills and Self-Confidence - Puspitasari, Nitta; Mardiani, Dian; Azaria, Rahma; Nuraeni, Reni; Noordyana, Mega Achdisty (Department of Mathematics Education Program IPI Garut, 2025)
Kemampuan komunikasi matematis dan self-confidence penting dalam pembelajaran matematika. Namun, banyak siswa masih mengalami kesulitan dalam mengungkapkan ide matematis dan kurang percaya diri dalam pembelajaran. Diperlukan model pembelajaran inovatif seperti Inquiry Learning dan Discovery Learning yang melibatkan siswa secara aktif. Penelitian bertujuan menganalisis perbedaan peningkatan kemampuan komunikasi matematis dan self-confidence antara siswa yang dibelajarkan dengan model Inquiry dan Discovery Learning, serta mengkaji hubungan antara kedua kemampuan tersebut. Metode yang digunakan adalah kuasi eksperimen dengan desain pretest-posttest nonequivalent control group. Data dikumpulkan melalui tes dan kuesioner, dianalisis menggunakan Independent Sample t-test dan uji t’ untuk membandingkan peningkatan, serta uji korelasi Pearson untuk melihat hubungan antar variabel. Hasil penelitian menunjukkan adanya perbedaan peningkatan kemampuan komunikasi matematis dan self-confidence antara kedua model pembelajaran. Namun, tidak ditemukan hubungan antara peningkatan komunikasi matematis dan self-confidence dalam masing-masing model. Mathematical communication skills and self-confidence are two important aspects in learning mathematics. However, many students still have difficulty expressing mathematical ideas and lack confidence in learning. Therefore, innovative learning models such as Inquiry Learning and Discovery Learning are needed that actively involve students. This study aims to analyze the differences in the improvement of mathematical communication skills and self-confidence between students who are taught with the Inquiry and Discovery Learning models, and to examine the relationship between the two abilities. The method used is a quasi-experiment with a nonequivalent control group pretest-posttest design. Data were collected through tests and questionnaires, then analyzed using the Independent Sample t-test and t' test to compare improvements, and the Pearson correlation test to see the relationship between variables. The results showed differences in the improvement of mathematical communication skills and self-confidence between the two learning models. However, no relationship was found between the improvement of mathematical communication and self-confidence in each model.